The impact of knowledge and innovation management on organisational performance in Gauteng-based pharmaceutical companies. - Peters, Jeremy James (My University, 2016)
Background The pharmaceutical industry is currently experiencing challenges that most companies within the industry are aware of. These include: the patent cliff, diminishing returns on investment, increasing expenditures, pricing pressures and fundamental changes in technology (Ahmed, 2014; Tidd, 2005). The industry attributes these challenges predominantly to externalities that are out of their control, instead of reassessing their internal dynamics and seeking solutions to overcome the challenges that persist. Knowledge and innovation are poorly managed in the South African pharmaceutical industry. Previous studies conducted across business sectors demonstrate that in order to remain competitive and to overcome the challenges that exist, managing both knowledge and innovation are the key drivers to achieving a better performing organisation (Berger, 2010). The impact of managing both knowledge and innovation on organisational performance was applied to the pharmaceutical industry in the Gauteng province of South Africa. Method This research made use of a quantitative paradigm and adopted a survey design as the primary means of collecting data. A total of 51 responses were obtained from an online survey questionnaire that was sent to middle and senior managers, including executive committee members of the top ten pharmaceutical companies based in South Africa. The three constructs used in this research were knowledge management, innovation and organisational performance. The impact of knowledge management, as the independent variable, was assessed on innovation and organisational performance employing Spearman’s-p correlation, multiple and simple linear regression techniques. The impact of innovation management on organisational performance was also analysed using Spearman’s-p correlation and simple linear regression. iii Results “Codification” and “Personalisation”, representing two dimensions of a KM strategy, had a positive correlation with innovation and organisational performance with statistically significant R-values ranging from 0.54 to 0.66 at 1 percent significance. Innovation showed a positive correlation with organisational performance with a significant R-value of 0.82 at 1 percent significance. Multiple linear regressions of the KM construct on both innovation and organisational performance portrayed acceptable significant fit statistics for each construct with adjusted R-square scores of 0.30 and 0.49 respectively at 1 percent significance. Further analyses of the individual dimensions of KM, codification and personalisation, revealed no major difference regarding the influence that either of these dimensions has on innovation and organisational performance, with more influence attributed to the dimension of codification. Simple linear regression of the innovation construct represented as the independent variable, and organisational performance as the dependent variable shows acceptable significant fit statistics for each construct with adjusted R-square score of 0.69 at 1 percent significance. Conclusion Codification and Personalisation, as part of a knowledge management strategy, proved to be a positive predictor of both innovation and organisational performance, however, an Innovation management strategy on its own proved to be more influential than a KM strategy in influencing the performance of an organisation.
MBA
Keywords: Knowledge management -- South Africa. Pharmaceutical industry -- South Africa. Technological innovations -- South Africa. Organizational learning -- South Africa.